Hubungan antara Locus Of Control dengan Kematangan Karier pada Mahasiswa: Tinjauan Literatur Sistematis - Dhila Ihsanul Hasanah; Rina Nurhudi Ramdhani; Agus Taufiq; Setiawati (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2023)
The large number of students who have not been able to decide what career choices they will pursue after graduating from university, as well as the high number of unemployed graduates, one of which is the background of their low career maturity. One of the factors that influence career maturity is locus of control. Locus of control describes how far the individual views his confidence in the efforts he makes to achieve a career. This study aims to describe the relationship between locus of control and career maturity in college students. This study uses a systematic literature review method with PRISMA guidelines. The data used is a collection of articles about locus of control and career maturity in students. The data comes from searching articles on the Google Scholar and Crossref databases with the help of the Publish or Perish (POP) application. The article search strategy uses keywords according to topics from the last 10 years, namely 2012-2022. The articles were screened and an assessment of the feasibility of the journal was carried out according to the inclusion and exclusion criteria. This study uses 6 main articles. The results showed that there was a significant relationship between internal locus of control and career maturity in college students. That is, the higher the student's internal locus of control, the higher the career maturity of the student.